Relationship of insight to neurocognitive function and risk of recurrence in depression: A naturalistic follow-up study - Wang, Min; Liu, Qiong; Yang, Xiao; Dou, Yikai; Wang, Yu; Zhang, Zijian; Luo, Ruiqing; Ma, Yangrui; Wang, Qiang; Li, Tao; Ma, Xiaohong (Frontiers in Psychiatry, 2023)
Introduction Major depressive disorder (MDD) is a highly recurrent mental illness accompanied by impairment of neurocognitive function. Lack of insight may affect patients’ motivation to seek treatment, resulting in poor clinical outcomes. This study explores the relationship of insight to neurocognitive function and the risk of recurrence of depressive episodes in patients with MDD. Methods Demographic, clinical variables, and neurocognitive function measured with Intra-Extra Dimensional Set Shift (IED) from the Cambridge Neuropsychological Test Automated Battery (CANTAB) were collected from 277 patients with MDD. Among them, 141 participants completed a follow-up visit within 1–5 years. Insight was measured using the 17-item Hamilton Depression Rating Scale (HAM-D). To explore the factors associated with recurrence, binary logistic regression models were used. Results Patients with MDD, without insight, had significantly higher total and factor scores (anxiety/somatization, weight, retardation, and sleep) on the HAM-D and worse performance in the neurocognition task, compared to those with insight. Furthermore, binary logistic regression revealed that insight and retardation can predict recurrence. Conclusion Lack of insight is associated with recurrence and impaired cognitive flexibility in patients with MDD.